2018
DOI: 10.1111/ans.14504
|View full text |Cite
|
Sign up to set email alerts
|

Method of pedicle division during laparoscopic right hemicolectomy affects lymph node yield and short‐term outcomes

Abstract: Lymph node yield after laparoscopic RHC is adequate, whether the vascular pedicle is taken intracorporeal or extracorporeal, supporting the use of both approaches. RHC-IC yields more lymph nodes and greater mesocolic width, but involves a longer operation and higher incidence of ileus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(21 reference statements)
1
1
1
Order By: Relevance
“…Short‐term complications including hemorrhage, ileus, anastomotic leak, and surgical site infections were similar between the two groups; the median length of stay was more or less similar. While a previous study [5] demonstrated a higher incidence of postoperative ileus in the intracorporeal group, this was not confirmed by our study. This difference might be associated with the wide adoption of enhanced recovery after surgery program in our department.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Short‐term complications including hemorrhage, ileus, anastomotic leak, and surgical site infections were similar between the two groups; the median length of stay was more or less similar. While a previous study [5] demonstrated a higher incidence of postoperative ileus in the intracorporeal group, this was not confirmed by our study. This difference might be associated with the wide adoption of enhanced recovery after surgery program in our department.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, intracorporeal vessel ligation was associated with more extensive colon excisions according to our results. This finding is consistent with a previous study by Pal et al [5] who reported a higher lymph node yield with intracorporeal vessel ligation in right colon surgery.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation